Creatine kinase in ischemic and inflammatory disorders. Issue 1 (15th August 2016) - Kitzenberg, David; Colgan, Sean P.; Glover, Louise E.
Abstract: The creatine/phosphocreatine pathway plays a conserved and central role in energy metabolism. Compartmentalization of specific creatine kinase enzymes permits buffering of local high energy phosphates in a thermodynamically favorable manner, enabling both rapid energy storage and energy transfer within the cell. Augmentation of this metabolic pathway by nutritional creatine supplementation has been shown to elicit beneficial effects in a number of diverse pathologies, particularly those that incur tissue ischemia, hypoxia or oxidative stress. In these settings, creatine and phosphocreatine prevent depletion of intracellular ATP and internal acidification, enhance post‐ischemic recovery of protein synthesis and promote free radical scavenging and stabilization of cellular membranes. The creatine kinase energy system is itself further regulated by hypoxic signaling, highlighting the existence of endogenous mechanisms in mammals that can enhance creatine metabolism during oxygen deprivation to promote tissue resolution and homeostasis. Here, we review recent insights into the creatine kinase pathway, and provide rationale for dietary creatine supplementation in human ischemic and inflammatory pathologies.